Alternating operating theatre utilization is not associated with differences in clinical or economic outcome measures in primary elective knee arthroplasty. (September 2019) - Murphy, William S.; Harris, Samantha; Pahalyants, Vartan; Zaki, Mark M.; Lin, Ben; Cheng, Tony; Talmo, Carl; Murphy, Stephen B.
Abstract : Aims: The practice of alternating operating theatres has long been used to reduce surgeon idle time between cases. However, concerns have been raised as to the safety of this practice. We assessed the payments and outcomes of total knee arthroplasty (TKA) performed during overlapping and nonoverlapping days, also comparing the total number of the surgeon's cases and the total time spent in the operating theatre per day. Materials and Methods: A retrospective analysis was performed on the Centers for Medicare & Medicaid Services (CMS) Limited Data Set (LDS) on all primary elective TKAs performed at the New England Baptist Hospital between January 2013 and June 2016. Using theatre records, episodes were categorized into days where a surgeon performed overlapping and nonoverlapping lists. Clinical outcomes, economic outcomes, and demographic factors were calculated. A regression model controlling for the patient-specific factors was used to compare groups. Total orthopaedic cases and aggregate time spent operating (time between skin incision and closure) were also compared. Results: A total of 3633 TKAs were performed (1782 on nonoverlapping days; 1851 on overlapping days). There were no differences between the two groups for length of inpatient stay, payments, mortality, emergency room visits, or readmission during the 90-day postoperative period. The overlapping group had 0.74 fewer skilled nursing days (95% confidence interval (CI) -0.26 to -1.22; p < 0.01), and 0.66 more home health visits (95% CI 0.14 to 1.18; p = 0.01) than the nonoverlapping group. On overlapping days, surgeons performed more cases per day (5.01 vs 3.76; p < 0.001) and spent more time operating (484.55 minutes vs 357.17 minutes; p < 0.001) than on nonoverlapping days. Conclusion: The study shows that the practice of alternating operating theatres for TKA has no adverse effect on the clinical outcome or economic utilization variables measured. Furthermore, there is opportunity to increase productivity with alternating theatres as surgeons with overlapping cases perform more cases and spend more time operating per day. Cite this article: Bone Joint J 2019;101-B:1081–1086.